1990
DOI: 10.1139/l90-095
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of low-temperature behaviour of cracks in asphalt pavement structures

Abstract: This paper examines the transient stress analysis of a multilayer pavement stmcture subjected to heat conduction and asssciated thefanoelastic effects by the cooling of its surface. In particular, the layered structure contains a transverse crack which can be created either during the construction of the pavement or during its service life-The numerical treatment of the transient stress analysis is achieved using a finite element scheme, which models the heat conduction and thermoelasticity of each component i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Positive and negative T-stress values can result in reduction or enhancement of the fracture resistance in cracked pavements. However in most of previous research studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17], the influence of such parameter has not been investigated for pavements with different geometrical and material characteristics subjected to traffic loading. Fig.…”
Section: Top-down Crack Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive and negative T-stress values can result in reduction or enhancement of the fracture resistance in cracked pavements. However in most of previous research studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17], the influence of such parameter has not been investigated for pavements with different geometrical and material characteristics subjected to traffic loading. Fig.…”
Section: Top-down Crack Resultsmentioning
confidence: 99%
“…Shalaby et al [12] also investigated the influence of thermal stresses on mode I crack growth behavior of cracked asphalt overlays using two and three-dimensional finite element models in ANSYS software. In another research work, Selvadurai et al [13] modeled low temperature cracking behavior of a multi-layer pavement structure subjected to thermal loads using the framework of fracture mechanics. Karadelis and Lin [14] computed the value of energy release rate at the interface of concrete/overlay pavement using crack closure method.…”
Section: Introductionmentioning
confidence: 99%
“…The attention is restricted to the examination of two-dimensional plane-strain problem in which the surface of the viscoelastic layer is subjected to a sudden decrease in the temperature, in the form of a step function of time. The results of a previous investigation [5] have shown that the rapid reduction in the surface temperature of an elastic asphalt layer results in the development of the maximum stress intensity factor at the crack tip. The geometry of the region in relation to the surface crack is shown in Fig.…”
Section: Surface Crack In a Viscoelastic Mediummentioning
confidence: 95%
“…In particular, the study of the mechanical behavior of pavement structures that are subjected to low-temperature effects is regarded as an important aspect of improving pavement performance and design. These studies become more important in situations where defects such as cracks, delaminations, voids, etc., are induced in the asphalt pavements and overlays either during its construction or during its service life 11-31, Recent studies [4,5] have examined the behavior of a pavement structure with a surface crack that is subjected to the combined effects of heat conduction and associated thermoelastic effects. Such surface cracks could be created either during construction of the asphalt layer or during its service life.…”
Section: Introductionmentioning
confidence: 99%
“…The composite materials are always assumed to be homogeneous and isotropic and their heterogeneous and anisotropic properties are largely ignored (Selvadurai et al 1990). …”
Section: Introductionmentioning
confidence: 99%